La inteligencia musical como estrategia para el desarrollo del proceso de enseñanza- aprendizaje en el quinto año educación general básica paralelo “B” en la Unidad Educativa “Pedro Vicente Maldonado” provincia de Chimborazo, cantón Riobamba, año lectivo 2020-2021. - Paguay Arias, Yadira Fernanda (2022)
The main objective of musical intelligence as a strategy in the teaching and learning process is to determine its importance and how it helps in the Teaching and Learning Process (PEA), since its presence identified in the students, and at the same time they relate it within the classroom. The purpose of this research work is to make known the benefits of developing musical intelligence as a tool to help students obtain more knowledge in other learning areas. The methodology used is mixed qualitative-quantitative, non-experimental, conducting field research to extract information from the source, where the results found that for a long time teachers seek the necessary strategies for their students to acquire the right tools that can build useful knowledge, and then they can apply it in their daily lives also that musical intelligence along with others such as mathematical intelligence, linguistic, bodily, naturalistic, spatial and those that make up what is now known as emotional intelligence. Learning to develop all these intelligences will allow us to obtain more job opportunities, it concluded that the strategy of the teaching-learning process proposed as a baseline for the implementation of more detailed projects, in this document the information of the source is raised, the same that validates to continue in the advancement of the strengthening of the career and its similar.